Antioxidant properties and total phenolic content in different development stages of Barringtonia racemosa and Barringtonia spicata leaves - Dhiya Dalila, Zawawi; Abd Manaf, Ali; Hafsah, Ja'afar (2015)
Barringtonia racemosa and Barringtonia spicata are moderate sized trees that can be found in Southeast Asia. They are medicinal plants that have been used in traditional practice to treat itching, high blood pressure, and as a depurative, by using their leaves. Due to the healing properties of the leaves, it is important to determine the antioxidant properties and total phenolic content from the different developmental stages of the leaves. It was assumed that the young leaves have a higher activity than mature ones. The total phenolic content (TPC) of the plant extract was determined alongside the free radical scavenging ability using a 1,1-diphenyl-2-picrylhydrazyl (DPPH) assay, and also the capacity of the extracts to inhibit lipid peroxidation by using a ferric thiocyanate (FTC) and thiobarbituric (TBA) assay. The highest TPC was observed in the methanolic extracts of the stage 1 leaves of B. racemosa (0.34 mg GAE/g DW) and B. spicata (0.19 mg GAE/g DW). The highest scavenging activity was shown in the methanolic extract from the stage 3 leaf of B. racemosa, with IC 50 at 33.33 µg/ml. In B. spicata, it was shown in stage 4, at 42.33 µg/ml, as compared to the chloroform extraction. All extracts actively inhibited lipid peroxidation with an amount of more than 88 % inhibition. The healing properties of Barringtonia could come from their high antioxidant activities. More detailed study will be required to identify which of the active compounds are present in the leaves that act as antioxidant compounds.